2019
DOI: 10.1177/1120672119889007
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral exudative retinal detachment in undiagnosed ocular syphilis after treatment with corticosteroids

Abstract: A case of a young Caucasian male who presented bilateral papilledema is described. He was misdiagnosed with bilateral anterior optic neuritis, developing panuveitis and exudative bilateral retinal detachment after being treated with megadoses of corticosteroids. He was finally diagnosed with ocular syphilis and treated with intravenous aqueous crystalline penicillin for 14 days, with complete resolution of his symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The first reason ocular syphilis is recognized as sight-threating is that it is easily misdiagnosed as a noninfectious eye disease and then erroneously treated with a systemic or local steroid which might cause irreversible visual loss. Deterioration of uveitis or optic neuritis and decreased vision were frequently reported in ocular syphilis patients misdiagnosed as non-infectious ocular inflammations (4,5). In this study, 22 cases were erroneously treated with oral steroid or peribulbar injection before ocular syphilis was diagnosed and all underwent visual deterioration.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…The first reason ocular syphilis is recognized as sight-threating is that it is easily misdiagnosed as a noninfectious eye disease and then erroneously treated with a systemic or local steroid which might cause irreversible visual loss. Deterioration of uveitis or optic neuritis and decreased vision were frequently reported in ocular syphilis patients misdiagnosed as non-infectious ocular inflammations (4,5). In this study, 22 cases were erroneously treated with oral steroid or peribulbar injection before ocular syphilis was diagnosed and all underwent visual deterioration.…”
Section: Discussionmentioning
confidence: 80%
“…Pratas et al reported that 75% of ocular syphilis cases had a good final visual outcome of best-corrected visual acuity (BCVA) ≥20/40 (1). Unfortunately, ocular syphilis may occasionally present as the only clinical manifestation of syphilis, and mimic other ophthalmic diseases such as non-infectious uveitis or optic neuritis, and therefore, can be easily misdiagnosed or erroneously treated with steroids which probably leads to irreversible visual loss (4,5). Gu et al reported that 23.5% of the late syphilis cases they researched met the WHO definition of blindness prior to treatment and patients with optic atrophy before treatment showed permanent visual loss.…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to a type II error as our sample size consisted of 18 eyes and may not have been sufficiently powered to detect differences in the timepoint of steroid initiation. It is also worth noting that no patients in our study received steroids prior to the initiation of the penicillin as this could potentially exacerbate the infection and result in poor patient outcomes [13]. The patients in this study were also all immunocompetent with CD4+ counts higher than 500; therefore, more research needs to be conducted to assess the risk and benefits of initiating steroids in patients with low CD4+ counts.…”
Section: Discussionmentioning
confidence: 98%